Abnormal Fibrin Clot Architecture in Nephrotic Patients Is Related to Hypofibrinolysis: Influence of Plasma Biochemical Modifications - Collet, Jean-Philippe; Mishal, Zohar; Lesty, Claude; Mirshahi, Manoucher; Peynet, Jacqueline; Baumelou, Alain; Bensman, Albert; Soria, Jeannette; Soria, Claudine (Thrombosis and Haemostasis, 1999)
Porosity, viscoelasticity and morphological properties of plasma fibrin from 16 nephrotic patients and 16 healthy volunteers were compared. Nephrotic patients were characterized by formation of tight and rigid plasma fibrin gels which resulted in a slower rate of fibrin lysis studied either under pressure-driven permeation or diffusional transport of fibrinolytic agents. These latter findings indicated that both abnormal fibrin network conformation and abnormal fibrin fiber structure were involved in hypofibrinolysis. Albumin supplementation up to 40 mg/ml partially restored normal fibrin architecture and increased the rate of fibrinolysis in these patients. Multiparametric analysis showed that nephrotic patients were mainly characterized by a low plasma albumin level (R = -0.85), a low albumin to fibrinogen ratio (R = -0.89) and a high resistance to lysis (R = -0.82). High triglycerides level was the only plasma modification related to the slower fibrin lysis rate (R = -0.54). High fibrin rigidity (G’) was the only fibrin parameter simultaneously related to the nephrotic state (R = 0.75) and the lysis resistance (R = -0.71). After eliminating the effects of age, albumin and fibrinogen levels, low fibrin porosity (Ks) and low fiber mass-length ratio (μ) were the main features of the nephrotic state. These findings are discussed in relation to both the pathophysiology of thrombotic complications in nephrotic syndrome and their pharmacological prevention.
Keywords: Fibrin; hypofibrinolysis; nephrotic syndrome